A&T Ethiopia Complementary Feeding Endline Survey 2017: Households - International Food Policy Research Institute (International Food Policy Research Institute, 2020)
This dataset is the result of the household survey that was conducted to gather data at endline as part of the study assessing the impact of the A&T social and behavior change communication (SBCC) interventions in the Amhara region of Ethiopia. A&T is a global initiative that supports the scaling up of nutrition interventions to save lives, prevent illnesses, and contribute to healthy growth and development through improved maternal nutrition, breastfeeding and complementary feeding practices. A&T's focus in this phase of the study in Ethiopia (with program implementation from late 2014 to 2017) is on operationalizing the IYCF component of the Government of Ethiopia’s National Nutrition Plan (NNP) in one region, Amhara. The objectives of the A&T initiative in Amhara are as follows: 1) Sustain high rates of EBF among children 0–5.9 months at over 70 percent in A&T program areas, 2) Increase the proportion of children 6–23.9 months of age who receive a diverse diet (at least four food groups) by 10 percentage points in A&T program area, and 3) Increase the proportion of breastfed and non-breastfed children 6–23.9 months of age who receive solid, semi-solid, or soft foods at least the minimum number of times per day by 10 percentage points in A&T program areas. A cluster-randomized design with repeated cross-sectional surveys at baseline (2015) and endline (2017) were used to assess impact of the A&T social and behavior change communication (SBCC) interventions in Amhara region, particularly the community-based interventions (interpersonal communication and social mobilization) and mass media activities. The evaluation includes household and frontline worker (FLW) surveys. Twenty woredas (districts) were purposively selected as potential areas of work by A&T HQ and Save the Children, and the select woredas were randomly assigned as 10 intervention (or A&T-intensive, A&T-I) and 10 comparison (or A&T-Non intensive, A&T-NI) woredas. A&T intervention areas were expected to receive intensive IYCF SBCC activities as well as exposure to a region-wide mass media campaign, while the comparison areas received standard health and agricultural services and exposure to mass media. The focus of this impact evaluation was on the intensive IYCF SBCC activities at the community level. The endline survey applied 5 questionnaires that aimed to capture elements along the program impact pathways: (1) household questionnaire and anthropometric measurements of children and mothers, (2) community questionnaire, (3) frontline worker questionnaire: Health extension worker (HEW), (4) Frontline worker questionnaire: Health development army team leader (HDATL), and (5) Frontline worker questionnaire: Agriculture development agent (ADA). A household roster was used to gather information on household composition and characteristics of each member (age, gender, and education). The endline household questionnaire was developed by adapting the baseline questionnaire to capture key program elements, particularly exposure to the A&T community-based interventions and mass media activities. The household questionnaire was administered to the mother of the index child selected for the survey. In addition to the questionnaire, anthropometric measurements (height and weight) were collected for mother and index child in each household.